THE PREVALENCE OF ANEMIA, KNOWLEDGE, AND NUTRIENT CONSUMPTION AMONGST PREGNANT WOMEN IN PUSKESMAS TAMPAKSIRING I, GIANYAR, BALI - Aryani, Putu; Laksmi Utari, Ni Made (Medicina, 2012)
According to the pregnant women’s registration data in Puskesmas Tampaksiring I, there were three cases of anemia in June 2007, which were occurred among the poor and less educated pregnant women. Therefore, the goals of this study were to determine the prevalence of anemia, knowledge and the nutrient consumption among pregnant women in Tampaksiring, Gianyar. The study was conducted from July 2007 to September 2007, used cross-sectional descriptive quantitative method. Data was collected by structured interview using questionaire and haemoglobin examination using the Sahli Method. A sample of 45 pregnant woman were choosen from the register in Puskesmas Tampaksiring. Results of the studies showed that 80% of the sample were suffering from anemia. The knowlegde of the sample about nutrition was divided into three categories, namely “good level of knowledge” (13.3%), “sufficient knowledge” (62.2%), and “insufficient knowledge” (24.4%). The consumption patterns did not support the iron and folic acid needs of these women. It was found that most of the sample’s diet contained more vegetables than fish or meat, which are known to be good sources of iron and folic acid. In addition, during pregnancy, they continued to drink coffee and tea, which inhibit the absorption of iron in small intestine. For nutritional intake during pregnancy, we found that levels of protein, vitamins A and  C were above the standard although intake of energy, calcium, Fe and vitamin B were below the recomended daily amounts.